Tagging: An Organization Scheme for the Internet - Visser, Marijke A. (Information Technology and Libraries, 2010)
How should the information on the Internet be organized? This question and the possible solutions spark debates among people concerned with how we identify, classify, and retrieve Internet content. This paper discusses the benefits and the controversies of using a tagging system to organize Internet resources. Tagging refers to a classification system where individual Internet users apply labels, or tags, to digital resources. Tagging increased in popularity with the advent of Web 2.0 applications that encourage interaction among users. As more information is available digitally, the challenge to find an organizational system scalable to the Internet will continue to require forward thinking. Trained to ensure access to a range of informational resources, librarians need to be concerned with access to Internet content. Librarians can play a pivotal role by advocating for a system that supports the user at the moment of need. Tagging may just be the necessary system.